The mediating role of step counts in the relationship between diverse neighbourhood destinations and older adults’ physical function - Chien-Yu Lin; Hsin-Yen Yen; Ming-Chun Hsueh; Jong-Hwan Park; Yung Liao (Scientific Reports)
Abstract Research has shown that access to activity-supportive neighbourhood destinations is associated with physical activity levels and physical functioning in older adults. However, the relative importance of different destinations and the mechanisms underlying these relationships remain unclear. We investigated (i) the relationships between the availability of diverse neighbourhood destinations and physical functioning in Taiwanese older adults and (ii) whether step counts mediated these relationships. Data were analysed from 206 participants aged 65 years or above, recruited from geriatrics outpatient clinics or check-up services at a medical centre in Taipei, Taiwan. Geographic information system technology was used to assess the availability of utilitarian destinations, public transport stations, parks, schools, and sports facilities based on geocoded addresses. Physical functioning was evaluated through on-site examinations. Logistic and linear regression models were used to investigate the relationships and joint-significance tests were used to examine mediation effects. The participants (52.4% women) were generally healthy, with no severe comorbidities, good cognitive function, and a low risk of depression. Adjusted models showed that greater park availability was associated with better physical functioning, including upper and lower limb strength and mobility. The relationship appeared to be partially mediated by increased step counts. Some evidence suggested that walking steps also mediated the relationship between the availability of public transport stations and physical functioning. However, no direct relationhips were found between public transport station availability and physical functioning, suggesting potential offseting factors. These findings suggest strategic allocation of neighbourhood resources, such as parks, to promote walking behaviour and enhance physical functioning in older adults. Future research should explore park design, usage patterns, and other potential mediators related to public transport stations to refine strategies for maintaining and improving physical functioning in ageing populations.